Synthesis and application of chitosan/graphene oxide/magnetite nanostructured composite for Fe(III) removal from aqueous solution - Truong, Le Dang; Tran Vinh Hoang; Thu, Le Dieu; Quang, Tran Ngoc; Hang, Nguyen Thi Minh; Khoi, Nguyen Dang; Trinh Xuan Anh; Tran Le Anh (Vietnam Journal of Science and Technology, 2018)
In this research, the potential of chitosan/Fe3O4/graphene oxide (CS/Fe3O4/GO) nanocomposite for efficient removal of Fe(III) a cationic metal ion from aqueous solutions was investigated. The synthesized CS/Fe3O4/GO was characterized by XRD, VSM and SEM techniques. Also, the various parameters affecting Fe3+ removal were investigated. Fe(III) adsorption equilibrium data were fitted well to the Langmuir isotherm and the maximum monolayer capacity (qmax), was calculated from the Langmuir as 6.5 mg.g-1. The results show that, CS/Fe3O4/GO nanocomposite, can be used as a cheap and efficient adsorbent for removal of heavy metal ions from aqueous solutions.